Avaliação da eficiência na captação de investimentos turísticos nas rotas turísticas do Espiríto Santo utilizando análise envoltória de dados - Baldo, Josiane (2011)
Tourism becomes a sector of more important time for the economic and social development of a country, contributing for the reduction of disparity of the regions and favoring for its growth. The transport service, as well as road infrastructure is essential part of the tourism in order to promote movement of tourists to the intended destination. The economic and social importance of the tourism sector has given rise to the need to study methods that can measure the power of attraction of their tourists destinations, beyond the efficiency in attracting investment in tourism in relation to investment in roads leading to these destinations. This paper presents a dissertation proposal which aims to apply the general methodology of Data Envelopment Analysis to measure the efficiency in the capture of Tourism Investment in relation to Investment in Highways in Tourist Routes of the Espírito Santo, and thus assistance the government in making decisions so that minimum standards of quality of road infrastructure and tourism are warranted to users. For this study were analyzed 87 stretches road linking Vitória to each urban community that compose these Courses. The stretch were divided into two groups due to the difference in the traffic volume with the primary reason the double track. Analyzes of the two groups and of the results achieved were made, and finally the conclusion of this paper is presented with proposals for future works.